Performance Study of a Two-Phase Handoff Scheme for Wireless ATM Networks - Salah, Khaled (1999)
This paper presents an analytical and simulation study of a two-phase handoff scheme for rerouting user connection in Wireless ATM networks. The two-phase handoff scheme provides a rapid rerouting of user connections in the first phase utilizing permanent virtual paths reserved between adjacent Mobility Enhanced Switches (MES). In the second phase, a non-realtime route optimization procedure is executed to optimally reroute handed-off connection. In this paper, we study the performance of such a scheme as a function of various system load parameters. These parameters include originating call arrival rate, call holding time, and radio cell residual time. We examine the relation between the required bandwidth resources and optimization rate. Also we calculate and study the handoff blocking probability due to lack of bandwidth for resources reserved to facilitate the rapid rerouting.